2016
DOI: 10.1073/pnas.1525518113
|View full text |Cite
|
Sign up to set email alerts
|

Human neural crest cells contribute to coat pigmentation in interspecies chimeras after in utero injection into mouse embryos

Abstract: The neural crest (NC) represents multipotent cells that arise at the interphase between ectoderm and prospective epidermis of the neurulating embryo. The NC has major clinical relevance because it is involved in both inherited and acquired developmental abnormalities. The aim of this study was to establish an experimental platform that would allow for the integration of human NC cells (hNCCs) into the gastrulating mouse embryo. NCCs were derived from pluripotent mouse, rat, and human cells and microinjected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 39 publications
2
67
0
Order By: Relevance
“…To further confirm the interspecies chimerism of hEPS cells, we employed a highly sensitive mitochondrial PCR assay to quantitatively analyze the degree of integration of hEPS cells in mouse conceptuses (Cohen et al, 2016; Theunissen et al, 2016). Notably, 34.4% of recovered hEPS-cell-derived mouse embryos (41/119 recovered embryos) contained human cells (we used 1 human cell in 10,000 mouse cells as the threshold).…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the interspecies chimerism of hEPS cells, we employed a highly sensitive mitochondrial PCR assay to quantitatively analyze the degree of integration of hEPS cells in mouse conceptuses (Cohen et al, 2016; Theunissen et al, 2016). Notably, 34.4% of recovered hEPS-cell-derived mouse embryos (41/119 recovered embryos) contained human cells (we used 1 human cell in 10,000 mouse cells as the threshold).…”
Section: Resultsmentioning
confidence: 99%
“…For example, human glial progenitor cells transplanted into the mouse brain are able to differentiate, mature and form a neural network with the neurons of the host animal (Han et al, 2013). Other progenitor cell types, for example neural crest cells, have also been used in interspecies chimeric assays (Cohen et al, 2016). In this case, the neural crest cells were derived in vitro from human PSCs and transplanted into the mouse embryos at the appropriate location and stage of development.…”
Section: Human Somatic Cell-derived Chimeras With Postimplantation Anmentioning
confidence: 99%
“…The donor cells, after transplanting into a developmental-stage matched host, should participate in normal embryonic development to generate functionally integrated human cells of the respective cell lineage. Using this approach, we showed that human neural crest stem cells transplanted into the gastrulating mouse embryo followed neural crest specific migration patterns and contributed to the pigment lineage in postnatal mice (Cohen et al, 2016). Importantly, genetic depletion of the host melanoblast lineage significantly increased integration of human cells, suggesting that an “empty host niche” gives donor cells a selective advantage to efficiently contribute to interspecies chimeras.…”
Section: Hpsc Models Of Complex Phenotypes - Interspecies Chimerasmentioning
confidence: 99%